Ballast Water Control and Management in Brunei Darussalam - Hjh Zuliza Hj Jolkifli; Ranimah H.A Wahab (ASEAN Journal on Science and Technology for Development, 2018)
The ongoing transfer of non-indigenous organisms through shipping, especially via ballast water transport, is placing marine and coastal resources under increased threat. The transport of Invasive Alien Species (IAS) is a critical issue which may cause irreversible consequences to receiving environments and economies needing particular attention. The main objective of this paper is to highlight the importance for implementation of ballast water management measures in Brunei Darussalam. This paper recognised IAS intrusion via ballast water has high probability to have direct effects on the economic value of fisheries sector, thus the need for an effective ballast water management strategy. Management of ballast water is a complex issue and horizontal policy is the appropriate approach for building this management framework in addition to valid baseline and efficient monitoring. Further studies such as development risk assessment model and assessment of different management measures are critical for an effective prevention, eradication and control strategy.